Bodies, violence, silencing: The transgenderity discourse (Letras & Letras, 2020)
By reflecting upon the discourse production conditions, the imagination of/on trans individuals and the temporal landmark of the 2018 elections in Brazil, I aim to analyze the relationship between silencing and resistance of/to the trans body in the virtual space. To this end, I selected two pieces of news posted on digital media, one about the play O Evangelho Segundo Jesus, Rainha do Céu[free translation: The Gospel According to Jesus, Queen of Heaven], which was interdicted in the Winter Festival of Garanhuns, State of Pernambuco, and the other about a ‘travesti’ murder in Sao Paulo. I analyzed these pieces to understand the dispute of meanings involving the trans corporeality based on the theoretical framework provided by the Materialist Discourse Analysis. Complementarily, I analyzed the comments on the news, as this is a space where the individuals, under the illusion that everything can be said, produce discourses in tune with the trans cause or hate discourses that delegitimize, make silent and displace meanings about such bodies.